ANALYSIS OF INTENTION TO USE THE PUBLIC SERVICE PROGRAM BASED ON THE TANGERANG LIVE APPLICATION AMONG CITIZENS IN TANGERANG CITY USING TECHNOLOGY ACCEPTANCE MODEL - Rizky Meviano, Azriel; Hanani, Retna (Journal of Public Policy and Management Review, 2025)
Public service digitalization is an important element in modern governance to improve efficiency, accessibility, and transparency. However, the implementation of digital applications often faces challenges, as found in the application "Tangerang Live," a digital public service platform from the Tangerang City Government. This study aims to analyze the factors that influence citizens' intention to use the application with the Technology Acceptance Model (TAM) framework, reviewing the influence of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) on Behavioral Intention to Use (BIU). A quantitative methodology was applied, collecting primary data through structured questionnaires from 107 purposively selected respondents who were residents of Tangerang City, had experience using the application, and were over 17 years old. The collected data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships between variables. The findings demonstrate that both perceived usefulness and perceived ease of use significantly and positively influence behavioral intention to use. This indicates that users are more inclined to adopt the "Tangerang Live" application when they perceive it as practical, time-saving, and easy to navigate.